A personal account of minor activities in the British agricultural war effort with some speculations on the application of British technique in Irish agricultural conditions - Fitzgerald, Kevin C. (Statistical and Social Inquiry Society of Ireland, 1947)
It was my fortunate lot to see something, at first hand, of the tremendous drive for increased food production, made almost as a single individual, by the whole of that great mass of men and women in the agricultural industry of Great Britain. Can this be done in Ireland? If it cannot, what is the reason? For Ireland produces some of the best farmers in the world, and because of their climate and the productivity of their soil, they have, as I have seen for myself, much spare time to devote to the serviced of their country. That is my Speculation No. 1. Speculation No. 2 concerns itself with the age-old problem, in Ireland, of winter dairying. Speculation No. 3 : What has happened in Irish livestock circles? Part of the British war effort was to intensify the fight against disease. Is enough being done here outside the efforts of some few dozen devoted men?
Read on Friday, 12th April, 1946
Keywords: British agricultural war effort; Agriculture, Ireland; 314.15